Perspectivas de la agricultura rural en el Ecuador: una mirada a la tecnología e innovación en el sector agropecuario - Mendoza León, Gabriela Jamileth (2023)
Technology and innovation are contributing to the economic growth of the agricultural sector, for which most producers worldwide invest part of their money to be able to access innovative agricultural technology, obtaining a high level of satisfaction to needs. that are presented in the agricultural sector using new components such as the innovation of machinery and training for producers, seeking to have a high quality of production and labor specialized in technology, which allows producers to increase greater economic income. The objective of this investigative work is to analyze the perspectives of rural agriculture in Ecuador: a look at technology and innovation in the agricultural sector. An investigative methodology was proposed with updated information from web pages, scientific articles, magazines, blogs and virtual libraries that are of all types of bibliographic material important for the proper development of this information. The results obtained so far today is the technological progress that is now used in the agricultural system by which the strategies are to seek improvement in the agricultural sector to establish a sustainable economy. This work concludes that technology and innovation in agriculture is highly focused on a comprehensive, extensive approach, where technology and innovation is the commitment and efforts that are aimed at promoting a favorable agricultural system.